Partisipasi Politik Paguyuban Kerukunan Keluarga Bima-Dompu Dalam Membangun Komunikasi Politik Lokal Di Kota Kupang - Idris Idris; Ambo Ambo; Nurdin Nurdin (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2020)
This paper attempts to answer the question of how the political participation of the Bima-Dompu family harmony community in building local political communication in Kupang City. The research method used is a qualitative approach. This study concludes that the political participation of the Bima-Dompu Community at the time of the regional head election of Kupang City still tends to be based on one-stop instructions where the community leader determines their political attitude.